Diabetes is the Leading Cause of ESRD in Haemodialysis Patients - Mahbub, Tania; Chowdhury, Md. Nizam Uddin; Jahan, Ferdous; Arefeen, Sakibjjaman; Rahman, Motlebur; Sarker, MS (Journal of Medicine, 2013)
Diabetes is one of the leading causes of ESRD and the no of diabetes patients is increasing day by day.In the developed world it is the first and foremost cause of renal failure. However in the developing countries it has been considered as second most common cause after GN.This study was a cross sectional study conducted during Oct 2010 to Sept 2011, in the dept of Nephrology, Dhaka Medical College and Hospital to determine the cause of renal failure with specific object to find out the leading cause of ESRD among the Haemodialysis patients. This study found Diabetes as the leading cause of ESRD accounting 44.1% of whole population. DOI: http://dx.doi.org/10.3329/jom.v14i1.14595 J MEDICINE 2013; 14 : 62-64